DIRECT METHODS IN X-RAY CRYSTALLOGRAPHY - Elmurotova Dilnoza Baxtiyorovna; Esanov Shaxzod Shermat o'gli; Sodiqov Farxod Husan o'g'li; Ibrohimov Suhrob Vahob o'g'li (Web of Journals Publishing, 2025)
The paper considers the history of the creation of a direct method of X-ray structural analysis. There are 230 combinations of symmetry elements that a crystal structure, which are called space groups. The Bragg X-ray diffraction scheme, the structure of a sandwich complex of a mercury-containing macrocycle with borane, and the atomic scattering curves for a point atom, a stationary atom, and an atom undergoing thermal vibrations are studied.
Keywords: X-ray structural analysis, combination, element, space, structure, scheme, diffraction, atom, scattering, vibrations.